Agricultural Chemicals as a Risk Factor For Intrauterine Fetal Hypotrophy In The Regions With Intensive Farming - Magomed G. Magomedov, Djamilya M. Magomedova, Shamayilpatimat M. Magomedova, Abdurrahman M. Samedov, Shamil M. Taymaskhanov, Islam S. Magomedov (International Journal of Advanced Science and Technology, 2020)
The present article describes the results of the retrospective study and the evaluation of high territorial loads (TL) of pesticides on the occurrence rate and spread of intrauterine fetal hypotrophy (IUFH) on the lowland, sub-mountain, and highland areas of Dagestan that are different by the rate of the studied pathology and the amount of the applied pesticides.